En verden til forskel. Stat og civilsamfundets indsats omkring idræt for vanskeligt stillede, overvægtige børn - La Cour, Annette Michelsen (Forum for Idræt, 2011)
Artiklen har til formål at vise, hvordan de strategier, foreningerne anvender i løsningen af velfærdspolitiske opgaver, kan bruges som modeller for et velfærdspolitisk samarbejde. Afsættet er en evaluering af en række idrætsprojekter for vanskeligt stillede børn. The article elaborates on the welfare political consequences of projects for disadvantaged target groups through volunteer-based sports associations. The analysis leads us through three analytical perspectives to elaborate on three models. 1. The welfare institutional model 2. The civil society institutional model 3. The health institutional model These analytical perspectives are joined together into the theoretical perspective, civicness or »substantive« civility. This can be related to a specific form of political support of civil society which creates solidarity behaviour and accountability within the frameworks of civil institutions. In such forms of governance, there will be a discursive relationship between ideology, form of control and inclusion of the third sector, which by allocating to civil society both importance and responsibility, succeeds in creating co-administration and solidarity – reflexive solidarity.